Web-based Proceedings Article Repository - Che Mohd Sakri, Norsyahira Shamilla; Wan Ishak, Wan Hussain (Multidisciplinary Applied Research and Innovation, 2023)
The number of proceeding articles has increased in recent years. Because they are not systematically managed, it is challenging to locate and recover a certain proceeding that people want. Therefore, a digital repository system is proposed in this study. This system can be used to share and distribute the proceedings articles. The goal of this project is to offer a long-term solution to the need for a system for storing and retrieving proceedings articles that is reliable, efficient, effective, and simple to use. This might increase the productivity and calibre of research. At the end of the project, it is expected that the normal user, admin, and organizer of the conference will be able to manage the proceedings articles and generate reports using the system. In this project, first, the functional requirements were gathered through the requirement analysis. Based on the requirements gathered, a prototype called the Web-based Digital Repository for Proceedings Articles (WDR) was constructed. A field study was then conducted to assess the prototype's usability. The evaluation's findings suggested that WDR is practical and simple to utilize. The functions for managing and retrieving the proceedings articles by WDR were likewise rated favorably by the respondents.